التواجد الرقمي للجامعة الجزائرية في الفضاء الافتراضي - الموقعين الإلكترونيين لجامعتي قالمة وسطيف1 نموذجا- (El-Wahat Journal for Research and Studies, 2023)
ملخص:منذ بروز معالم الإعلام الجديد بوسائله وتقنياته سارعت المؤسسات لمجارات تطوراته وإعادة صياغة هيكلة طريقة عملها وبرامجها فراحت تضع معايير وبدائل مرنة، للتعايش مع البيئة الرقمية التي فرضت عليها التكيف مع مخرجاتها، إضافة للتفاعلية والتواصل.تسعى الباحثة من خلال هذه الدراسة إلى تقييم الحضور الرقمي للجامعات الجزائرية في الفضاء الافتراضي والذي مثله الموقع الالكتروني الرسمي ومدى احترامه للشروط العالمية لتصميم المواقع، ومن النتائج المتوصل لها بعد تحليلنا لبنية الموقعين أن كلاهما )موقع جامعة 8 ماي 1945 قالمة وموقع جامعة فرحات عباس سطيف 1(، أثبتا حضورا رقميا اختلفت فيه كلا الجامعتين في طريقة العرض والطرح، لمختف الأعمال البيداغوجية والنشاطات اليومية، إضافة لتوظيف مختلف سائل الاعلام الجديد للتواصل وإثبات الحضور الرقمي.كلمات دالة : التواجد الرقمي، الفضاء الافتراضي، الموقع الإلكتروني للجامعة، المحتوى الرقمي الأكاديمي.     Abstract : Since the emergence of the features of the new media with its means and technologies, institutions hastened to keep pace with its developments and reformulate their method of work and programs, so they set standards and flexible alternatives, to coexist with the digital environment, which forced them to adapt to their outputs in addition to interactivity and communication. Through this study, the researcher seeks to evaluate the digital presence of Algerian universities in the virtual space, which is represented by the official website and the extent to which it respects the international conditions for web design, and the results obtained after analyzing the structure of the two sites (the website of the University of  8 May 1945 Guelma and the website of Farhat Abbas Setif University 1) That both of them demonstrated a digital presence in which both universities differed in the way they presented and presented the various educational work and daily activities, in addition to employing various new media to communicate and prove the digital presence. Key words: digital presence, virtual space, university website, academic digital content.